Validity and Reliability of the Pfizer Booster Vaccine Effectiveness Questionnaire - Raihan Fadhil Muhammad; Diana Laila Ramatillah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Vaccination is the right method to deal with the increasing number of infections due to COVID-19. One method for assessing the effectiveness of a vaccine is by using a questionnaire. This pilot study was conducted to assess the validity and reliability of the Pfizer booster vaccine effectiveness questionnaire in Indonesia. The pilot study was carried out cross-sectionally using a new questionnaire that had not been tested for validity and reliability. The validity test of the questionnaire was carried out using the modified Delphi method which 3 professional will determine whether the questionnaire is valid to be used while in reliability analysis using inter reliability consistency analysis with score not less than < 0.3. Based on the collected data, there are 25 (62.5%) female respondents and 15 (37.5%) male respondents. With the age of majority <30 years as many as 37 (92.5%) respondents, <45 as many as 2 (5%) respondents and >45 as many as 1 (2.5%) person.. In the validity test, 3 experts stated that the questionnaire is considered to be valid and suitable for use in research. Before checking the inter reliability consistency there were 50 questions but after the analysis only 12 questions were considered reliable to be used with Cronbach's alpha score 0.797. Of the 12 questions, there were 3 questions on sociodemography, 3 questions on side effects, 4 questions on allergy history, and 2 questions on data regarding history of COVID-19 infection. It can be concluded that the questions are considered valid by 3 experts and has 12 reliable questions in this questionnaire with Cronbach's alpha of 0.797. Although it functions as a pilot study for questionnaire development, its significance lies in the potential to enhance our understanding of the various factors that impact the effectivness of the pfizer booster vaccine, specifically within the Indonesian population.Keyword: Cronbach's Alpha, Pfizer, Reliability, Vaccines, Validity